2020
DOI: 10.4155/bio-2020-0041
|View full text |Cite
|
Sign up to set email alerts
|

Automation of RNA-Based Biomarker Extraction From Dried Blood Spots for the Detection of Blood Doping

Abstract: Aim: Transcriptomic biomarkers originating from reticulocytes measured in dried blood spots (DBSs) may be reliable indicators of blood doping. Methods/results: Here, we examined changes in the expression levels of the erythropoiesis-related ALAS2, CA1 and SLC4A1 genes in DBS samples from elite athletes and volunteers of clinical study with recombinant erythropoietin dose. Conclusion: By comparing the mean intraday coefficients of variation for ALAS2L, ALASLC, CA1 and SLC4A1 between manual and automated RNA ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 27 publications
3
27
0
Order By: Relevance
“…17 Moreover, previous studies done by our group on RNAbased biomarkers for indirect detection of rhEPO use demonstrate that ALAS2 LC, ALAS2 L, CA1, and SLC4A1 mRNAs can be detected using DBSs. 5,6 The present study confirms that RNA-based biomarkers could offer a viable solution for increasing the sensitivity and specificity of the ABP. Furthermore, the method reported here provides a solution for distinguishing between variations due to rhEPO use and variations due to hypoxia exposure using DBSs as the matrix.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…17 Moreover, previous studies done by our group on RNAbased biomarkers for indirect detection of rhEPO use demonstrate that ALAS2 LC, ALAS2 L, CA1, and SLC4A1 mRNAs can be detected using DBSs. 5,6 The present study confirms that RNA-based biomarkers could offer a viable solution for increasing the sensitivity and specificity of the ABP. Furthermore, the method reported here provides a solution for distinguishing between variations due to rhEPO use and variations due to hypoxia exposure using DBSs as the matrix.…”
Section: Introductionsupporting
confidence: 79%
“…mRNA was extracted manually from DBSs and analyzed as described by Loria et al 6 using the miRNeasy Mini Kit (Qiagen, Germany), following the manufacturer's instructions with minor modifications. 5,6 After being cut from the collection card, the whole DBS was transferred into a 2-ml conical polypropylene microcentrifuge tube (Eppendorf, Switzerland). The cells were lysed by adding 1-ml QIAzol lysis reagent (Qiagen) to the tube and agitated (450 rpm) at 37 C for 15 min.…”
Section: Rna Extraction and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…31,81 Recent advancements in instrumentation have achieved improved accuracy and sensitivity which has led to magnified attention in the use of microsamples. 42,46,[80][81][82] The range of applications include therapeutic drugs, [83][84][85][86] biomarkers, 87,88 proteins and peptides, 89 drugs of abuse, 90,91 hormones and steroids, 92,93 DNA/RNA 56,87 and cytokines. 27,53,94 Few established applications discussed below focus on the use of microsampling techniques in the determination of drug concentration using a validated bioanalytical method.…”
Section: Applications Of Microsampling In the Development Of Treatmentsmentioning
confidence: 99%
“…Leuenberger and colleagues have shown that an automated method of analysis they used for transcriptomic biomarkers from reticulocytes in dried blood spots was as good as or better than manual sample handling. They applied their methodology to examine changes in the expression levels of a number of factors in samples from elite athletes and volunteers after recombinant erythropoietin injection [9].…”
mentioning
confidence: 99%